An Analysis of TPACK (Technological Pedagogical Content Knowledge) Implementation by Novice English Teacher in EFL Context: Technological Consideration and Technological Innovation - Ni Komang Indah Pratiwi; I G A Lokita Purnamika Utami; I Putu Indra Kusuma (Jurnal IKA, 2026)
The rapid advancement of technology in the global era requires educators to master the Technological Pedagogical Content Knowledge (TPACK) framework as a foundation in integrating technology into the English teaching process in a targeted manner. This study aims to examine the influence of TPACK mastery on technological consideration and technological innovation for beginner English teachers in the context of English as a Foreign Language (EFL). A qualitative approach with a basic qualitative design was applied through semi-structured interviews and hands-on classroom observation, involving five English teachers with less than five years of teaching experience in a number of junior high schools in Buleleng Regency. Inductive thematic analysis yielded two main findings. First, understanding TPACK encourages teachers to choose digital devices reflexively and experiment with innovative learning strategies such as gamification, interactive multimedia, and collaborative platforms. Second, novice teachers face a number of significant obstacles, namely the lack of professional training, limited digital infrastructure, difficulties in aligning technology with specific language skills, low student readiness, and high administrative burden. These findings underscore the urgency of professional development programs that integrate the dimensions of technology, pedagogy, and content holistically to support the effectiveness of technology-based English teaching.